2020
DOI: 10.2196/17221
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Perceptions of Barriers and Facilitators to the Adoption of E-Hospitals: Cross-Sectional Study in Western China

Abstract: Background As an innovative approach to providing web-based health care services from physical hospitals to patients at a distance, e-hospitals (ie, extended care hospitals through the internet) have been extensively developed in China. This closed health care delivery chain was developed by combining e-hospitals with physical hospitals; treatment begins with web-based consultation and registration, and then, patients are diagnosed and treated in a physical hospital. This approach is promising in i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 59 publications
1
46
4
Order By: Relevance
“…Contrary to a previous study regarding eHealth use and age [ 35 ], we found that older women spent more time on the BCS program and the Learning Forum than younger women. In the abovementioned study, although older people were less likely to use eHealth intervention, the age disparity was found to be related to technological proficiency [ 35 ]. In this study, the user-centered design of the BCS program may help older women to alleviate their concern regarding technological ability [ 27 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to a previous study regarding eHealth use and age [ 35 ], we found that older women spent more time on the BCS program and the Learning Forum than younger women. In the abovementioned study, although older people were less likely to use eHealth intervention, the age disparity was found to be related to technological proficiency [ 35 ]. In this study, the user-centered design of the BCS program may help older women to alleviate their concern regarding technological ability [ 27 ].…”
Section: Discussioncontrasting
confidence: 99%
“…A previous study found that employed participants showed more interest in eHealth [ 35 ] and benefited more from eHealth [ 39 ]. Similarly, employed women used our BCS program more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…5 6 Nevertheless, when discussing the integration of telemedicine into healthcare systems, it is important to consider the barriers that may prevent successful adoption. [7][8][9][10][11][12][13] First, only 8.1% (447 of 5517) of physicians at WCH used the telemedicine platform. A recent physician survey at WCH identified the following potential challenges: lack of time, insufficient authenticity and reliability and underdeveloped policies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, older patients, while most reliant on healthcare services, are less likely to use telemedical applications. 8 Therefore, hospitals must ensure that access to online assistance is available for patients, such as those from older cohorts, that lack technological proficiency, in order to successfully care for patients from all demographics. Along with prioritising user-friendliness and providing access to technical assistance, it is compulsory that patients are well aware that online healthcare services exist.…”
Section: Discussionmentioning
confidence: 99%
“…The PubMed search led to 35 results, of which 16 articles were included for analysis after the title and abstract assessment (Supplementary Material A). Nine of the identified studies focused on self-management support (40)(41)(42)(43)(44)(45)(46)(47)(48), two were related to health education and information (49,50), and five studies investigated digital health services (51,52) or health promotion and disease prevention interventions (53-55).…”
Section: Innovation Competitiveness Economic Growth and Digital Inmentioning
confidence: 99%